2018
DOI: 10.1088/1361-6579/aae6df
|View full text |Cite
|
Sign up to set email alerts
|

Can exercise-induced muscle damage be related to changes in skin temperature?

Abstract: Objective: Measurement of skin temperature using infrared thermography has become popular in sports, and has been proposed as an indicator of exercise-induced muscle damage after exercise. However, the relationship between skin temperature and exercise-induced muscle damage is still unclear. Here we set out to investigate the relationship between skin temperature and exercise-induced muscle damage. Approach: Twenty untrained participants completed a protocol of exercise for calf muscles. Before and after exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
1
9
1
1
Order By: Relevance
“…Their findings point out that thermography can be appointed together with CK. However, Da Silva et al [39] correlated CK and thermographic images, and it was observed that there was no correlation between the two variables after a muscle injury induction protocol, so it can be said that in a real situation-matches and training diaries-like the one investigated in our study, and laboratory situations, it is not possible to see a correlation between biomarkers of muscle damage with the increase in skin temperature.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Their findings point out that thermography can be appointed together with CK. However, Da Silva et al [39] correlated CK and thermographic images, and it was observed that there was no correlation between the two variables after a muscle injury induction protocol, so it can be said that in a real situation-matches and training diaries-like the one investigated in our study, and laboratory situations, it is not possible to see a correlation between biomarkers of muscle damage with the increase in skin temperature.…”
Section: Discussioncontrasting
confidence: 55%
“…It is known that the peak of delayed-onset muscle soreness (DOMS), as well as the increase in creatine kinase, are between 48 and 72 hours after physical activity [28,40]. Studies in the literature use the 48-hour window [18,39] after a physical effort to apply IRT, following the same window of CK responses and DOMS. Nevertheless, as mentioned before, it was not possible to observe a correlation among these variables in this window between physical effort and evaluation.…”
Section: Plos Onementioning
confidence: 99%
“…We measured the temperature before, during, and 10 min after exercise. When skin temperature was measured at the same time as DOMS in a previous study, no relationship was found [ 20 ]. Our data cannot support the use of skin temperature to predict the magnitude of muscle damage resulting from exercise and causing DOMS.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of skin temperature by infrared thermography can also provide non-invasive information about the efficiency of the thermoregulatory system in dissipating heat [ 18 ]. In a previous study, electrical manifestations of muscle fatigue (i.e., the mean and peak frequency of electromyography signals) were not considered in relation to skin temperature [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although sCK and sLDH are considered good indicators of muscle damage [ 11 ], other indirect tools have been used to decrease the invasive procedure during blood collection, such as using visual analog scales to measure DOMS [ 12 ]. Although the monitorization of baseline skin temperature (Tsk) using infrared thermography (IRT) was another methodology proposed, the results of the different investigations are contradictory [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%